Targeting complete response with upfront bortezomib consolidation versus observation after the achievement of complete response following autologous transplantation for multiple myeloma (TUBA study). Issue 1 (6th July 2017) - Nakasone, Hideki; Terasako‐Saito, Kiriko; Hirano, Teiichi; Wake, Atsushi; Shimizu, Seiichi; Kurita, Naoki; Yamazaki, Etsuko; Usuki, Kensuke; Akazawa, Kohei; Kanda, Junya; Minauchi, Koichiro; Yamamoto, Go; et al.
Abstract: Complete response (CR) after treatment for multiple myeloma is associated with superior progression‐free survival (PFS). Multiple myeloma patients were prospectively recruited for induction treatment with bortezomib and dexamethasone (BD) followed by autologous hematopoietic cell transplantation (auto‐HCT) between 2010 and 2012. If patients did not achieve CR after auto‐HCT, BD consolidation therapy was added to target CR. After the BD induction phase ( n  = 46), greater than or equal to CR was achieved in 4 patients (8%). After auto‐HCT ( n  = 34), greater than or equal to CR was achieved in 9 patients (20%) and very good partial response (VGPR) was achieved in 11 (24%). Of the 24 patients who received auto‐HCT and whose response was less than CR, 21 received BD consolidation therapy for a median of 4 courses. Finally, the maximum response with or without BD consolidation was greater than or equal to CR in 19 (41%), VGPR in 7 (15%), and PR in 6 (13%). Through BD consolidation, CR was achieved in 8 of 11 patients with post‐HCT VGPR and in 2 of 12 patients with post‐HCT PR. In total, 4 year PFS and overall survival were 43 and 80%, respectively. After adjusting for clinical factors, there was no difference in PFS between CR patients after auto‐HCT and BD consolidation, while patients with less than or equal to VGPR after consolidation had a significantly lower PFS. Patients with post‐HCT CR showed good PFS, and targeting CR through BD consolidation could improve the CR rate. It would be worthwhile to prospectively compare the efficacy of consolidation only for patients who failed to achieve CR to a universal consolidation strategy.